(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The importance of performance evaluation in many complex problems of management and policies of the supply chain area is sensed more than before. One of the main researches that are still in absence in the performance of a supply chain is to improve the overall efficiency based on the dynamic performance with measure Capacity Utilization (CU). In this paper, by developing the basic Dynamic Data Evolution Analysis (DDEA) model, as an efficient tool that is a new research focus for evaluating the CU of a supplier-manufacturer dynamic supply chain is studied. Also considering the time of performance evaluation with CU measure and variable inputs utilization rate, in order to demonstrate the growth or decline inputs of the supply chain has the key role in effective evaluating of the supply chain. At the end, the result of these offered models is shown through a numeric example.